Leituras da colonialidade à brasileira a partir de Manoel Bomfim - Silva, Gislania de Freitas (2023)
The objective of this research is to rescue Manoel Bomfim’s social and political thinking as well as to build up once again his professional performance as a teacher, in terms of the structuring of what he considered to be the way to solve the problems of Brazil. To this effect, it is required, on the methodological level, the understanding of Bomfim’s production, taking as a frame of reference the context in which his works were written, paying special attention to the social configurations to which the author had been subjected. The hypothesis is that his ideas are attuned to those of other insurgent intellectuals in Latin America, pointing to what is now predicated as postcolonial criticism studies, in the various ways these very studies have surfaced so far. This research is supported by Norbert Elias’s (1970; 1994; 1997; 2001) figurational theory; by Pierre Bourdieu’s (2004; 2017) concept of field of science; by Syed Farid Alatas’s (2001; 2003. 2010) concept of alternative discourses; by the concept of coloniality as it is presented by both Aníbal Quijano (2003; 2009) and Paulo Henrique Martins (2019). Bomfim produced a vast work analyzing the Brazilian society, naming some of the peculiarities (i) of the structuring process of national identity, (ii) of the problems faced by the Brazilian people, and (iii) of what he regards as the original evils. Discarding racialized explanations, rather common in the cultural repertoire of the author’s time and place, Manoel Bomfim took on a historical survey of Iberia, as he sought the ramifications which had crossed the Atlantic and had arrived in Brazil influencing aspects of national political culture and focusing on the construction of the Brazilian State. He highlighted the conservative ways of national elites as a remarkable feature which obstructed the development of popular demands, such as free education and tax reform which encumber the poor people’s meager resources, as well as the privileges of the ruling classes. Bomfim questioned the foundations of scientific objectivity, to what he opposed the feeling of affection as the research center part. He suggested the observance of facts of society on our own terms, without the dominance of foreign lenses which had marked national history up to his context. Such ideas set him apart from his peers and marked him as a transitional intellectual, who was coming from a specific perspective of science, that one grounded in racialized assumptions, to another one, in which such assumptions are refuted as science and as a moral principle. Therefore, throughout this research, we have highlighted Bomfim’s contributions to the formation of Brazilian social thought.